From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Reading Realness - Oishi, Eve (A Companion to Contemporary Documentary Film, 2015)
This essay performs a critical comparison of two documentary films about queer and trans people of color, Jennie Livingston's Paris is Burning (1991) and Wu Tsang's Wildness (2012) and examines how the two films negotiate of the politics of representing reality and “realness.” The comparison illuminates two entwined problematics: the ways in which the challenges faced by each film are emblematic of the larger historical context in which they were made, specifically notions of queer community and its subjects; and the ways in which the negotiation of these challenges occurs in relation to a broader field of ethical and formal questions relating to documentary itself.
Section: 12 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch12
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé